Investigation of ototoxicity of artesunate as add-on therapy in patients with metastatic or locally advanced breast cancer: new audiological results from a prospective, open, uncontrolled, monocentric phase I study - König, Miriam; Hagens, Cornelia von; Hoth, Sebastian; Baumann, Ingo; Walter-Sack, Ingeborg; Sertel, Serkan (Cancer chemotherapy and pharmacology, 2016)
Purpose Artesunate (ART) has been used for a long time in the treatment of Plasmodium falciparum malaria and has been considered safe. The present phase I study aimed to determine the daily dose of ART that is well tolerated as add-on therapy in patients with breast cancer for 4 weeks of therapy. Ototoxicity could be a potential safety concern in settings different from malaria. Therefore, comprehensive audiological assessment was essential.MethodsThe ARTIC M33/2 study was a prospective, open, uncontrolled, monocentric phase I dose-escalation study to evaluate the safety and tolerability of ART in patients with advanced breast cancer. Patients received either 100, 150 or 200 mg oral ART daily for a test phase of 4 weeks as add-on therapy to their ongoing oncological treatment. For the investigation of the safety of ART for hearing, an audiological assessment was performed with each patient before the intake of ART and after 4 weeks of therapy.ResultsTwenty-three female patients were included in the study. During the test phase, four patients had adverse events (AEs) of the auditory system possibly related to the intake of ART. However, none of these AEs was classified as severe AE (SAE) and did not require treatment interruption. Four patients had AEs concerning the vestibular system (vertigo) during the test phase, one of which was classified as SAE. However, the SAE was fully reversible after discontinuation of ART.ConclusionNone of the audiological results after 4 weeks of therapy with ART showed any dose-limiting auditory toxicity. However, audiological monitoring in further clinical studies with prolonged use of oral ART in doses up to 200 mg daily is warranted.The ARTIC M33/2 study is registered at eudract.ema.europa.eu with the Number 2007-004432-23 and at clinicaltrials.gov with the Number NCT00764036.